2003
DOI: 10.1046/j.1365-2265.2003.t01-1-01755.x
|View full text |Cite
|
Sign up to set email alerts
|

Update on genetic and clinical aspects of primary hyperparathyroidism

Abstract: SummaryPrimary hyperparathyroidism (pHPT) is a common endocrine disorder that predominantly affects postmenopausal women. It is mostly caused by solitary tumours within the parathyroid glands. Although the pathophysiology of pHPT is still incompletely understood, recent studies provide new clues on the development and cellular growth of tumours within the parathyroids associated with hypersecretion of parathyroid hormone and hypercalcaemia. The natural course of pHPT is rather benign. Nowadays, it has become a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 196 publications
(245 reference statements)
0
18
0
4
Order By: Relevance
“…As a consequence of the high racial admixture of our population, it is extremely difficult, if not impossible, to appropriately separate the different Brazilian ethnic groups. Calcium and vitamin D deficiencies have been related to the clinical profile of PHP (18). Moosgaard et al (19) demonstrated that vitamin D deficiency or insufficiency is a common finding in PHP patients and occurs more often than in gender-and age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the high racial admixture of our population, it is extremely difficult, if not impossible, to appropriately separate the different Brazilian ethnic groups. Calcium and vitamin D deficiencies have been related to the clinical profile of PHP (18). Moosgaard et al (19) demonstrated that vitamin D deficiency or insufficiency is a common finding in PHP patients and occurs more often than in gender-and age-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…These heritable forms are responsible for approximately 10% of primary HPT. They are usually seen in the context of syndromes, such as multiple endocrine neoplasia types 1 and 2 (MEN 1, MIM #131100 and MEN 2, MIM #171400, respectively), hyperparathyroidism-jaw tumor syndrome (HPT-JT, MIM #145001), familial benign hypocalciuric hypercalcemia (FHH, MIM #145980) and familial isolated hyperparathyroidism (FIHP, #145000) (1). FIHP is a rare autosomal dominant condition, characterized by the occurrence of familial hyperparathyroidism in the absence of other associated lesions or endocrinopathies, with a clinical and genetically heterogeneous presentation (2)(3)(4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanism underlying defective calcium-sensing in parathyroid tumors is still not clear. Many authors have shown that both mRNA content and protein expression of CaSR are reduced in parathyroid adenoma tissue; however, the reduction is variable and independent of investigated clinical parameters such as serum calcium and PTH concentrations or tumor mass [25,26]. It is interesting that downregulation of CaSR appears associated with increased cellular proliferation, although the precise mechanism of the association remains unknown [26].…”
Section: Pathophysiology Of Pth-dependent Hypercalcemic Disordersmentioning
confidence: 97%